Combining in situ measurements and altimetry to estimate volume - Berx, Barbara; Hansen, Bogi; Østerhus, Svein; Larsen, Karin Margretha; Sherwin, Toby; Jochumsen, Kerstin (Ocean Science, 2013)
From 1994 to 2011, instruments measuring ocean currents (Acoustic Doppler Current Profilers; ADCPs) have been moored on a section crossing the Faroe–Shetland Channel. Together with CTD (Conductivity Temperature Depth) measurements from regular research vessel occupations, they describe the flow field and water mass structure in the channel. Here, we use these data to calculate the average volume transport and properties of the flow of warm water through the channel from the Atlantic towards the Arctic, termed the Atlantic inflow. We find the average volume transport of this flow to be 2.7 ± 0.5 Sv (1 Sv = 106 m3 s–1) between the shelf edge on the Faroe side and the 150 m isobath on the Shetland side. The average heat transport (relative to 0 °C) was estimated to be 107 ± 21 TW (1 TW = 1012 W) and the average salt import to be 98 ± 20 × 106 kg s−1. Transport values for individual months, based on the ADCP data, include a large level of variability, but can be used to calibrate sea level height data from satellite altimetry. In this way, a time series of volume transport has been generated back to the beginning of satellite altimetry in December 1992. The Atlantic inflow has a seasonal variation in volume transport that peaks around the turn of the year and has an amplitude of 0.7 Sv. The Atlantic inflow has become warmer and more saline since 1994, but no equivalent trend in volume transport was observed.